The occurrence of dystonia in upper-limb multiple sclerosis tremor. (December 2015) - Van der Walt, A; Buzzard, K; Sung, S; Spelman, T; Kolbe, SC; Marriott, M; Butzkueven, H; Evans, A
Background: The pathophysiology of multiple sclerosis (MS) tremor is uncertain with limited phenotypical studies available. Objective: To investigate whether dystonia contributes to MS tremor and its severity. Methods: MS patients ( n = 54) with and without disabling uni- or bilateral upper limb tremor were recruited (39 limbs per group). We rated tremor severity, writing and Archimedes spiral drawing; cerebellar dysfunction (SARA score); the Global Dystonia Scale (GDS) for proximal and distal upper limbs, dystonic posturing, mirror movements, geste antagoniste, and writer's cramp. Results: Geste antagoniste, mirror dystonia, and dystonic posturing were more frequent and severe ( p < 0.001) and dystonia scores were correlated with tremor severity in tremor compared to non-tremor patients. A 1-unit increase in distal dystonia predicted a 0.52-Bain unit (95% confidence interval (CI) 0.08–0.97), p = 0.022) increase in tremor severity and a 1-unit (95% CI 0.48–1.6, p = 0.001) increase in drawing scores. A 1-unit increase in proximal dystonia predicted 0.93-Bain unit increase (95% CI 0.45–1.41, p < 0.001) in tremor severity and 1.5-units (95% CI 0.62–2.41, p = 0.002) increase in the drawing score. Cerebellar function in the tremor limb and tremor severity was correlated ( p < 0.001). Conclusions: Upper limb dystonia is common in MS tremor suggesting that MS tremor pathophysiology involves cerebello-pallido-thalamo-cortical network dysfunction.